Characterization Of Oil Palm Shell Nano Filler In Hybrid Kenaf/Coconut Fibres Reinforced Polyester Composites - Wan Othman, Wan Nornadirah (2014)
In this research, hybrid kenaf/coconut fibres reinforced polyester composites were developed and enhanced with nano filler Oil Palm Shell (OPS). Dalam kajian ini, komposit poliester yang diperkuat gentian kenaf/kelapa hibrid telah dibangunkan dan ditingkatkan lagi dengan kemasukan pengisi nano tempurung kelapa sawit (OPS).